Impacts of COVID-19 shelter in place across key life domains among immigrant farmworker Latina mothers and young adults - Michael Bakal; Elizabeth Ambriz; Lizbeth Ortiz-Pivaral; Katherine Kogut; Claire Snell Rood; Stephen Rauch; Brenda Eskenazi; Julianna Deardorff (BMC, 2024)
Abstract Objective Individuals and families from racial and ethnic groups experience social and economic disadvantage making them vulnerable to the disproportionate impact of the COVID-19 pandemic. This study sought to capture the impacts of Shelter in Place (SIP) across key life domains including family life, education, work, mental health, and coping strategies among a sample of Mexican-origin mothers who were currently engaged in agricultural work, or whose spouses were engaged in agricultural work, and young adults who had a parent working in agriculture. Method During the summer of 2020, while California was under SIP orders, we conducted three virtual focus groups using Zoom(r). We recruited focus group participants from the Center for the Health Assessment of Mothers and Children of Salinas (CHAMACOS), an ongoing, 20-year, longitudinal cohort study of Mexican-origin families in a predominantly agricultural area of California. Three focus groups were conducted with mothers (n = 9), mean age = 48 years, young adult women (n = 8) and young adult men (n = 5), mean age = 18 years, respectively. Results Mothers reported high levels of stress stemming from fear of Covid-19 infection, work instability and financial concerns, children's schooling, anxiety about an uncertain future, and the demands of caretaking for dependents. Adverse mental health impacts were particularly pronounced among participants experiencing multiple adversities pre-dating the pandemic, including unemployment, single motherhood, and having undocumented family members. For young adults, work instability and varying work hours were also a source of stress because they made it difficult to make decisions about the future, such as whether to attend college or how many classes to take. Families used coping strategies including expressing gratitude, focusing on what's under one's control, familismo, and community engagement to manage mental health challenges during SIP. Conclusion In the event of future pandemics or disasters, particular attention is needed to those who experience unemployment, are undocumented and/or have undocumented family members, and/or are single parents facing economic adversity. During public health emergencies, action at the local, state, and national level is needed to support farmworkers and other vulnerable groups' secondary major stressors stemming from inequities in access to affordable housing, childcare, living wages, healthcare, and other benefits.